2017
DOI: 10.1111/nmo.13124
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution anorectal manometry: A comparison of solid‐state and water‐perfused catheters

Abstract: Greater sensitivity to rapid pressure change is one of the advantages associated with SS HR-ARM. This is reflected in the differences observed during dynamic maneuvers performed during this study. Catheter type should be taken into consideration when selecting normal ranges for comparison to disease states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
2
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 42 publications
2
30
2
4
Order By: Relevance
“…In contradiction to our study, Jones et al found that solid‐state high‐resolution manometry measured resting pressures higher than conventional water‐perfused manometry. HRAM measured squeeze pressure 27% higher than conventional manometry which is comparable to the findings of Jones et al Rasijeff et al compared solid‐state with water‐perfused HRAM and found no difference in resting pressure; however, squeeze pressure measurements were significantly higher when using solid‐state HRAM. Therefore, normal ranges for CM cannot be applied to HRAM and studies using CM and HRAM cannot be compared without adjustments.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In contradiction to our study, Jones et al found that solid‐state high‐resolution manometry measured resting pressures higher than conventional water‐perfused manometry. HRAM measured squeeze pressure 27% higher than conventional manometry which is comparable to the findings of Jones et al Rasijeff et al compared solid‐state with water‐perfused HRAM and found no difference in resting pressure; however, squeeze pressure measurements were significantly higher when using solid‐state HRAM. Therefore, normal ranges for CM cannot be applied to HRAM and studies using CM and HRAM cannot be compared without adjustments.…”
Section: Discussionsupporting
confidence: 75%
“…Making direct comparisons in the normal range data is hampered by differences in the statistical definitions of normality, the different manometric techniques, and variations in protocols. The most comparable study is by Rasijeff et al who performed water‐perfused HRAM on 60 healthy volunteers and established similar normal values. One difference was the lower limit of normal for squeeze increment was higher in our study for both male and female (76 vs 36 cmH 2 O for female and 143 vs 49 cmH 2 O for male, this study vs Rasijeff).…”
Section: Discussionmentioning
confidence: 68%
“…In a comparative study between the two systems, Rasijeff et al demonstrated similar numbers for the resting pressure, but it shows higher values for pressures obtained by the solid state method with respect to contention effort, which they suggest maybe attributable to the probe's faster response and sensitivity. In the end, it reviews and compares several publications and recommends that the values of normality should be computed for each system (13) . Wang Al et al, when analyzing 126 volunteers, obtained results equivalent to those of the present study when the values were not classified according to the sex of the participants (14) (TABLE 2).…”
Section: Discussionmentioning
confidence: 99%
“…Numerical results should approximate and homogenize the different populations. Clinical applicability and indications will be much more grounded and defined, and the parameters obtained in patients with pelvic dyssynergia may better guide their treatment (13,(16)(17)(18)(19) . This volumetric study (vector volume) can bring new information to the functional and anatomical aspects and prove its usefulness by iconographic representation (20) .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, existing normative data sets need to be extended to take into account age, sex, parity, and gender [26,48,49,[62][63][64][65][66][67][68][69][70][71][72][73][74][75]. Lack of standardization for interaction of the investigator with the patient and feedback during the investigation also increase variance of reported normal values and possibly the rate of DD seen with ARM [65,68].…”
Section: Current Limitationsmentioning
confidence: 99%